Thyroid Function and Thyroglobulin Level in Iodine-Deficient Children of Eastern Nepal - Kunwar, Saroj; Khatiwada, Saroj; Gelal, Basanta; Thapa, Saroj; Shah, Gaurishankar; Baral, Nirmal; Lamsal, Madhab (Nepal Journal of Biotechnology, 2021)
Iodine deficiency during childhood affects physical and mental development. Iodine deficiency or excess both can negatively impact thyroid function. We conducted this study to assess iodine nutrition and thyroid function in children with insufficient urinary iodine concentration. A community-based cross-sectional study was conducted among the selected schools of Udayapur district. Urinary iodine concentration (UIC) was measured in 1012 school children (6-14 years). Based on UIC data, 83 blood samples were collected to measure serum thyroglobulin (Tg), thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4). UIC was measured by ammonium persulfate digestion method, and Tg, TSH, fT4, and fT3 were measured using ELISA kits. The median UIE was 236 µg/L, and 11.1% of the children had insufficient UIC. The mean fT3, fT4, and TSH in children with insufficient UIC were 2.55±0.43 pg/mL, 0.96±0.28 ng/dL, and 3.60±1.44 mIU/L respectively. Among children with low UIC levels, the median Tg was 17.5 ng/mL. Overt hypothyroidism was seen in 6%, and subclinical hypothyroidism in 3.6%. The children had sufficient iodine nutrition, and the frequency of thyroid dysfunction was low among the children with insufficient UIC.